The Role of Faculty Members in Enhancing Self-Learning Skills among Students of the Faculty of Education A field study from the students' point of view - ناصر, إناس; مطيعة أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to identify the role of faculty members in enhancing self-learning skills among students of the Faculty of Education, as well as to identify the differences in the possession of self-learning skills among students of the Faculty of Education according to some variables (specialization and academic year), using the descriptive approach. The sample included (224) male and female students, students of the Faculty of Education from the disciplines (child rearing "classroom teacher", and psychological counseling), for the academic year 2022-2023. To achieve the objective of the research, a questionnaire was designed consisting of (24) items, distributed on three axes: (self-learning planning skills, self-learning implementation skills, and evaluation of self-learning skills). The results of the research showed that the overall degree of identifying the role of faculty members in enhancing self-learning skills among students of the Faculty of Education from their point of view was moderate. And the existence of statistically significant differences between the average opinions of students on the identification of the role of faculty members in enhancing self-learning skills according to the variable of specialization for the benefit of class teacher students. As well as the existence of statistically significant differences between the average opinions of students on the identification of the role of faculty members in enhancing self-learning skills according to the variable of the academic year, in favor of the last year students